CALCULATION OF THE IMPROPER INTEGRALS FOR FOURIER BOUNDARY ELEMENT METHOD - Łukasik, Edyta; Pańczyk, Beata; Sikora, Jan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The traditional Boundary Element Method (BEM) is a collection of numerical techniques for solving some partial differential equations. The classical BEM produces a fully populated coefficients matrix. With Galerkin Boundary Element Method (GBEM) is possible to produce a symmetric coefficients matrix. The Fourier BEM is a more general numerical approach. To calculate the final matrix coefficients it is necessary to find the improper integrals. The article presents the method for calculation of such integrals.